2022
DOI: 10.1128/spectrum.01697-22
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity of Ceftolozane-Tazobactam, Ceftazidime-Avibactam, and Cefiderocol against Multidrug-Resistant Pseudomonas aeruginosa Recovered at a German University Hospital

Abstract: After testing ceftolozane-tazobactam, ceftazidime-avibactam, and cefiderocol against a collection of 233 multidrug-resistant (MDR) Pseudomonas aeruginosa , we showed that cefiderocol is the most active antipseudomonal β-lactam agent (susceptibility rates were 46.6%, 48.4%, and 97.4%, respectively). The most prevalent one was sequence type 235 (ST235) (24.7%), followed by ST244, ST175, and ST233, with all belonging to the top 10 P. aeruginosa high-risk clones with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 43 publications
1
9
0
Order By: Relevance
“…All bacterial isolates were carbapenem-resistant (MIC > 8 mg/L) [ 15 ]; they are summarized in Table 1 and shown in Figure 3 . The most isolated bacteria were CRAB (75.6%).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All bacterial isolates were carbapenem-resistant (MIC > 8 mg/L) [ 15 ]; they are summarized in Table 1 and shown in Figure 3 . The most isolated bacteria were CRAB (75.6%).…”
Section: Resultsmentioning
confidence: 99%
“…The main real-life studies regarding CFD are reported in Table 4 . The 30-D mortality in these studies ranged from 12.5 to 60% [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. This wide variability is probably due to the different conditions of the patients described in these studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The choice of antimicrobial agents for treating infections caused by MBL-producing P. aeruginosa is limited because MBL-producing P. aeruginosa often plays resistance to a variety of antimicrobial agents (including carbapenems and ceftazidime-avibactam). It is gratifying that several current antimicrobial agents showed good in vitro activity against MBL-producing P. aeruginosa , such as cefiderocol and cefepime-zidebactam ( 23 , 24 ). In this study, the susceptibility of cefiderocol and cefepime-zidebactam were not affected by the expression of PDC-16 .…”
Section: Discussionmentioning
confidence: 99%
“…; Enterococcus spp. ; Acinetobacter spp., Clostridium difficile , and other resistant pathogens (such as carbapenemase makers) [ 64 , 65 , 66 , 67 ].…”
Section: New Antibiotics Therapymentioning
confidence: 99%